Pengaruh Gaya Kepemimpinan, Reward dan Lingkungan Kerja Terhadap Kinerja Karyawan (Studi CV. Asia Setia Putera) - Aditya Dwi Permana Putra; Hadi Sunaryo; Fahrurrozi Rahman (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract CV. Asia Setia Putera is a company operating in the cigarette industry. The problem of this study is that there are problems related to the decline in employee performance. The purpose of this study is to analyze the Influence of Leadership Style, Reward, and Work Environment on the Performance of CV.Asia Setia Putera Employees. This study used quantitative methods. Populai in this study is a permanent employee of CV.Asia Setia Putera. The approach method that uses non-probability sampling techniques is saturated sampling as a sample of 43 respondents. The tests carried out are instrument tests, classical assumption tests, multiple linear regression analysis tests and hypothesis tests using spss 22 software. The results showed that (1) Leadership Style has a positive and significant effect on Employee Performance, (2) Environment has a positive and significant effect on Employee Performance, Rewards have a negative and insignificant effect on Employee Performance. Based on the results that negatively affect the reward variable, this research can be used as the next research material to be applied in different places. Keywords: The Leadership Style, Reward, Work Environment, Employee Performance